The paleoecology of Pleistocene birds from Middle Bed II, at Olduvai Gorge, Tanzania, and the environmental context of the Oldowan-Acheulean transition. Issue 120 (July 2018) - Prassack, Kari A.; Pante, Michael C.; Njau, Jackson K.; de la Torre, Ignacio
Abstract: Fossil bird data (community composition and taphonomic profiles) are used here to infer the environmental context of the Oldowan-Acheulean transitional period at Olduvai Gorge, Tanzania. This is the first comprehensive report on the Middle Bed II avifauna and includes fossils excavated by the Olduvai Geochronology and Archaeology Project (OGAP) and recently rediscovered fossils collected by Mary Leakey. Crane, ibis, darter, owl, raptor, crow, and vulture are reported from Bed II for the first time. The presence of these taxa, absent earlier in this Bed, point to a general opening and drying of the landscape with grassland and open woodland expansion. Taxa associated with dense, emergent wetland vegetation, such as dabbling ducks and rails, are uncommon and less diverse than earlier in Bed II. This suggests more mature wetlands with clearer waters. Cormorants continue to be common, but are less diverse. Cormorants and other roosting taxa provide evidence of trees in the area. Compared to lowermost Bed II, the Middle to Upper Bed II landscape is interpreted here as more open and drier (but not necessarily more arid), with matured wetlands, scattered trees, and a greater expansion of grasslands.